(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This scientific article examined the improvement of preventive measures aimed at reducing cardiovascular disease risk factors among men over 40 years of age. The study identified that unhealthy diet, physical inactivity, harmful habits, and arterial hypertension are the leading risk factors for cardiovascular diseases. It was determined that promoting a healthy lifestyle, implementing regular medical examinations, and increasing health literacy play an important role in effective prevention. Based on the obtained results, strengthening preventive programs at both individual and population levels was found to be effective in reducing cardiovascular disease risk, and the implementation of comprehensive preventive measures for men over 40 years of age is recommended.